Study on the Mechanism of Influencing Adolescents' Willingness to Participate in Ice Sports - Zhuoling Liu; Sai Wang; Qian Gu (MDPI AG, 2023)
Background: Ice sports are an effective means to promote the physical health of adolescents, and the willingness to participate in ice sports is the basis of adolescents' awareness of their participation in ice sports and an important prerequisite for their participation. The aim of this study is to investigate the mechanisms influencing adolescents' willingness to participate in ice sports. Methods: Using the stimulus-organism-response theoretical framework, the motivation-opportunity-ability model, and the technology acceptance model, a theoretical model of the influencing mechanisms of adolescents' participation in ice sports was constructed. A total of 3419 secondary school students were surveyed, and the data were analyzed using structural equation modeling, the mechanisms influencing adolescents' willingness to participate in ice sports and the moderating role of perceived riskiness and perceived ease of use are proposed and tested. Results: The study found that participation motivation, participation ability, perceived usefulness, and perceived risk all have significant effects on adolescents' willingness to participate in ice sports. The degree of influence in descending order is as follows: ability to participate, perceived usefulness, motivation to participate, and perceived risk. Perceived risk plays a mediating role in the process of motivation to participate and ability to participate influencing willingness to participate. Perceived ease of use plays a mediating role in the process of motivation to participate influencing perceived usefulness. Conclusions: This study provides a systematic understanding of the mechanisms that influence adolescents' willingness to participate in ice sports. The findings provide valuable insights into the subject of adolescents' ice sport participation and can inform the development of strategies to increase participation in these activities. Future research should deepen the investigation of the patterns of willingness to participate in ice sports behavior among adolescents, which is important for promoting the sustainable development of ice sports, improving the health of adolescents, and advancing the construction of a healthy China, a healthy world, and global health.